A Ratio to Evaluate Harvest Procedures Management in an Economic System where Resources Dynamics is ruled by an Ornstein- Uhlenbeck Process - Ferreira, M. A. M.; Filipe, J. (arXiv:2110.00322, 2025)
The assessing resources dynamics problem, in the context of an economic system with Gaussian consumption and deterministic productivity, is considered in this paper. Basically it is presented a discrete time recursive equation that supports the recourse to the Ornstein-Uhlenbeck diffusion process. Some assumptions on the regeneration of the process are made, in order to observe the system equilibrium in what concerns the resources depreciation or accumulation. The objective of this work is to present a result on the sign of a ratio that can be used to evaluate harvest procedures in this context.